Efektivitas Berpikir Komputasi Dalam Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa - Nugroho, Bakti Adi Nugroho; Nalim (STAI Al-Bahjah, 2025)
This study aims to determine the effectiveness of the application of computational thinking in improving the mathematical problem-solving abilities of class X students of SMK Negeri 4 Pekalongan City. Computational thinking includes the ability of decomposition, abstraction, pattern recognition, and algorithm design, which play an important role in supporting the process of solving problems systematically. In the researcher's observation at SMK Negeri 4 Pekalongan City, it was shown that the learning process was still conventional with expository methods that did not use computational thinking, this expository method was carried out through monotonous lectures. The process was usually limited to teachers delivering material, giving practice questions, checking student assignments, and giving homework. As a result, students were less interested in developing their problem-solving abilities. The type of research used was quantitative with a quasi-experimental design of the nonequivalent control group design type. The research sample consisted of two classes, namely the experimental class and the control class. Data were collected through tests, observations, and documentation, then analyzed using the N-Gain test, normality test, and independent sample t-test. The results showed that the application of computational thinking effectively improved students' mathematical problem-solving abilities. In the experimental class, the average student score increased from 42.57 to 82.14, while in the control class it increased from 41.25 to 76.94. The higher increase in the experimental class indicates that students better understand the stages in solving problems. The t-test results show a Sig. (2-tailed) value = 0.019 < 0.05, while the average N-Gain value of 0.67 is included in the moderate category. Thus, learning with computational thinking is proven to be effective in improving students' mathematical problem-solving abilities.